1983
DOI: 10.1111/j.1745-9125.1983.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Institutional Misconduct Among State Prisoners

Abstract: A s with participation in illegitimate activities in the larger society, involvement in rule infractions within prisons is not normally distributed among prisoners. Rather, a small segment of the inmate population is disproportionately represented in official records of disciplinary activity. I n this research, factors associated with differential levels of involvement in prison disciplinary infractions were examined.The findings indicate that the inmate's age at commitment, history of drug use, current offens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 25 publications
12
120
0
4
Order By: Relevance
“…This was done because of a previously reported relationship between seriousness of index offence and inmate misconduct (cf. Flanagan, 1983;Wooldredge, 1991;DeLisi et al, 2004). The offences ranged from murder or manslaughter (30 detainees), robbery or carjacking (184 detainees), attempted murder (20 detainees), and aggravated assault (113 detainees) down to technical violations of probation (see also Haapanen and Steiner, 2006).…”
Section: Index Offencementioning
confidence: 99%
“…This was done because of a previously reported relationship between seriousness of index offence and inmate misconduct (cf. Flanagan, 1983;Wooldredge, 1991;DeLisi et al, 2004). The offences ranged from murder or manslaughter (30 detainees), robbery or carjacking (184 detainees), attempted murder (20 detainees), and aggravated assault (113 detainees) down to technical violations of probation (see also Haapanen and Steiner, 2006).…”
Section: Index Offencementioning
confidence: 99%
“…However, it is doubtful the differences in age can discount the present results, as there is no empirical evidence connecting younger inmates with improvements in these measures. In fact, studies specific to criminal infractions have found that younger inmates incur more infractions than older inmates (Faily, Roundtree, & Miller, 1980;Flanagan, 1983). Nonetheless, selection bias is a potential confound, which should be addressed in future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Most of these other factors are from cross-sectional research. Two of these factors are age and sentence length (Brown & Spevacek, 1971;Flanagan, 1980;Flanagan, 1983;Goetting & Howson, 1986;Myers & Levy, 1978). Being young and having a longer sentence are correlated with higher rates of misconduct.…”
Section: Introductionmentioning
confidence: 99%